103k views
5 votes
Multiply (4x-3w)(5x-7w)

2 Answers

7 votes

Answer:


20 {x}^(2) - 43xw + 21 {w}^(2)

solution,


(4x - 3w)(5x - 7w) \\ = 4x(5x - 7w) - 3w(5x - 7w) \\ = 20 {x}^(2) - 28xw - 15xw + 21 {w}^(2) \\ = 20 {x}^(2) - 43xw + 21 {w}^(2)

Hope this helps...

Good luck on your assignment..

User Asics
by
5.6k points
4 votes

Answer:

20x² - 43xw + 21w²

Explanation:

We use FOIL to expand the expression:

F - First

4x(5x) = 20x²

O - Outside

4x(-7w) = -28xw

I - Inside

-3w(5x) = -15xw

L - Last

-3w(-7w) = 21w²

20x² - 28xw - 15xw + 21w²

Combine like terms and add up using correct signs and you should get your answer.

User Cody C
by
5.9k points